Integrasi Ilmu dan Praktik dalam Manajemen Syariah - Jessika Gafur Lamba; Irwan Misbach; Okta Nofri (Yayasan Darussalam Patalassang, 2025)
This paper examines the intersection between the philosophy of science (epistemology, methodology, and ontology) and the development of Islamic management theory and practice. Using a critical literature review (library research), the study explores how Islamic epistemological foundations — including revealed sources and rational inquiry — shape paradigms, methods, and objectives in Islamic management (manajemen syariah). The review finds that integrating philosophy of science with maqāṣid al-sharīʿah and Islamic epistemology fosters a management model that pursues not only economic efficiency but also social welfare, justice, and ethical accountability. Recommendations include developing multi-method research approaches (hermeneutic-theoretical combined with empirical methods), embedding shariah values into performance metrics, and involving religious scholars in organizational policy design. Theoretical and practical implications for scholars, policymakers, and Islamic organizational.